Learning shifts the preferred theta phase of gamma oscillations in CA1. Issue 9 (3rd August 2022) - Rayan, Abdelrahman; Donoso, José R.; Mendez‐Couz, Marta; Dolón, Laura; Cheng, Sen; Manahan‐Vaughan, Denise
Abstract: Hippocampal neuronal oscillations reflect different cognitive processes and can therefore be used to dissect the role of hippocampal subfields in learning and memory. In particular, it has been suggested that encoding and retrieval is associated with slow gamma (25–55 Hz) and fast gamma (60–100 Hz) oscillations, respectively, which appear in a nested manner at specific phases of the ongoing theta oscillations (4–12 Hz). However, the relationship between memory demand and the theta phase of gamma oscillations remains unclear. Here, we assessed the theta phase preference of gamma oscillations in the CA1 region, at the starting and junction zones of a T‐maze, while rats were learning an appetitive task. We found that the theta phase preference of slow gamma showed a ~180° phase shift when animals switched from novice to skilled performance during task acquisition. This phase‐shift was not present at the junction zone, where animals chose a right or left turn within the T‐maze, suggesting that a recall/decision process had already taken place at the starting zone. Our findings indicate that slow gamma oscillations support both encoding and retrieval, depending on the theta phase at which they occur. These properties are particularly evident prior to cognitive engagement in an acquired spatial task.